Contextual innovation management : adapting innovation processes to different situations - Duin, P. A. van der (Patrick A.); Ortt, Roland J. (New York : Routledge, 2020)
'Innovation has a pivotal role for companies in attaining business survival but making an organization innovative is not straightforward. By determining contextual factors, managers can help decide how to employ a portfolio of innovation management processes. This book explores how contingency influence the management of innovation. Taking the perspective of innovation managers, the authors focus on the decision-making process to demonstrate that different approaches are required depending on the business context. In breaking the process into three levels (culture, industry and company), the book helps choose an optimal innovative approach. With references to real-world innovation cases and organizations, this book will prove useful reading for students and researchers in the field of innovation studies and management'--
Includes bibliographical references and index.
Keywords: Management -- Technological innovations; Technological innovations -- Economic aspects